2020
DOI: 10.1158/0008-5472.can-19-2330
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Haspin Kinase Promotes Cell-Intrinsic and Extrinsic Antitumor Activity

Abstract: Patients with melanoma resistant to RAF/MEK inhibitors (RMi) are frequently resistant to other therapies, such as immune checkpoint inhibitors (ICI), and individuals succumb to their disease. New drugs that control tumor growth and favorably modulate the immune environment are therefore needed. We report that the small-molecule CX-6258 has potent activity against both RMisensitive (RMS) and-resistant (RMR) melanoma cell lines. Haspin kinase (HASPIN) was identified as a target of CX-6258. HASPIN inhibition resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…Micronuclei and gross nuclei induced by all drugs tested showed strong cGAS enrichment (Figure 2C). These observations show that cGAS localization to micronuclei is not a reliable proxy for cGAS activation, contrary to assumptions in recent papers (Gratia et al, 2019; Melms et al, 2020).…”
Section: Resultscontrasting
confidence: 99%
“…Micronuclei and gross nuclei induced by all drugs tested showed strong cGAS enrichment (Figure 2C). These observations show that cGAS localization to micronuclei is not a reliable proxy for cGAS activation, contrary to assumptions in recent papers (Gratia et al, 2019; Melms et al, 2020).…”
Section: Resultscontrasting
confidence: 99%
“…In this work, we utilized the Chk1/2i inhibitor, AZD7762 in conjunction with ionizing radiation to provide proof of principle that pharmacologically forcing cell cycle progression following genotoxic stress is able to cause a resultant increase in the formation of micronuclei. This builds upon models shown in prior work indicating that cell cycle progression through mitosis coupled with DNA damage are the necessary factors for micronuclei formation 11 , 16 , and that cell cycle checkpoint kinase inhibition can drive mitotic catastrophe, inflammatory signaling, and cell-intrinsic and extrinsic anti-tumor activity 25 , 31 , 34 . Furthermore, we show that the combination treatment leads to increased expression of IFN-β mRNA and protein in vitro and an effect on an abscopal (unirradiated) tumor in vivo with increased expression of genes involved in immune activation and increased CD8+ T-cell infiltration, consistent with an increased systemic immune response.…”
Section: Discussionsupporting
confidence: 61%
“…Further, in agreement with our finding, a very recent study using CRISPR/Cas9 screening also identified a synthetic lethal interaction between Haspin inhibition and the pan-Aurora (A and B) kinase inhibitor VX680 in HCT116 colon carcinoma cells [60]. However, at odds with our finding, the authors found that the pan-Aurora (A and B) inhibitor VX-680 played a synthetic lethal role by targeting Aurora-B, but not Aurora-A.…”
Section: Discussionsupporting
confidence: 91%